Peningkatan Kesadaran Masyarakat Tentang Pentingnya Kebersihan Lingkungan Melalui Penyediaan Tempat Pembuangan Sampah Di Desa Lembah Sari Kecamatan Batu Layar - Dini Andriani; Lisa Andriani; Nurmaya Nurmaya; Erlin Erlin; Adriana Wahyuningsi; Inong Febrianti; Rahmad Hidayat; M. Ulfatul Akbar Jafar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The problem of waste has often been discussed in various fields, which is a complicated problem for people who are less concerned and less sensitive to environmental pollution. A clean and healthy environment is very important for welfare, especially for the people of Lembah Sari Village, West Lombok Regency. Like in many other places, the issue of environmental cleanliness is often a major concern. This is the background for the author to carry out Real Work Lecture service in one of the villages in the Batu Layar sub-district, West Lombok Regency, namely Lembah Sari Village. The method for implementing this activity program is: preparation stage, implementation stage, final stage. This community service activity in Lembah Sari Village is where the community is very happy with the provision of making rubbish bins in their village environment and it is very helpful in changing their mindset about the importance of keeping the environment clean. It is hoped that in the future this community service will continue to pay attention to maintaining environmental cleanliness, the habit of throwing rubbish away and leaving it there needs to be changed.